Comparison study between multicontrast atherosclerosis characterization (MATCH) and conventional multicontrast MRI of carotid plaque with histology validation. Issue 3 (24th August 2016) - Dai, Yuanyuan; Lv, Peng; Lin, Jiang; Luo, Rongkui; Liu, Hao; Ji, Aihua; Liu, Hui; Fu, Caixia
Abstract : Purpose: To compare Multicontrast ATherosclerosis Characterization (MATCH) with conventional multicontrast magnetic resonance imaging (MRI) in the characterization and quantification of carotid plaque components. Materials and Methods: Fifty‐three consecutive patients underwent carotid plaque 3.0T MRI including conventional multicontrast sequences and MATCH, with 13 of them having carotid endarterectomy for histology validation. The detection of major plaque components including lipid‐rich necrotic core (LRNC), loose matrix (LM), intraplaque hemorrhage (IPH), and calcification (CA) and measurement of lumen area, outer wall area, normalized wall index (NWI), and plaque components areas were compared between the two protocols. Results: Plaque analysis and comparison were done on 298 matched cross‐sectional MRI. MATCH detected significantly more calcifications than conventional consequences ( P < 0.01). The difference in detection of IPH ( P  = 0.07) and LRNC ( P  = 0.10) approached significance. There was no significant difference in demonstration of LM ( P =0.52). A larger area of IPH and CA was measured on MATCH ( P < 0.01). The difference nearly reached significance between the two protocols in measuring lumen area ( P  = 0.09) and outer wall area ( P  = 0.08). No significant difference was found when measuring the mean area of LRNC ( P  = 0.15) and LM ( P  = 0.14) and NWI ( P  = 0.38). By using receiver operating characteristic curve (ROC) analysis, the accuracy of MATCH and conventional protocols did not differ significantly in the detection of IPH ( P  = 0.15), LRNC ( P  = 0.61), LM ( P  = 0.48), and CA ( P  = 0.11) when histology served as a reference. Conclusion: MATCH was comparable if not superior to conventional protocol in identification and quantification of major carotid plaque components. Level of Evidence: 1 J. Magn. Reson. Imaging 2017;45:764–770.